Interregional features in the taxonomic composition of the Russian segetal floras - O. G. Baranova; A. S. Tretyakova; N. N. Luneva; A. A. Zverev; P. V. Kondratkov; T. A. Terekhina; G. R. Khasanova; S. M. Yamalov; M. V. Lebedeva (Труды по прикладной ботанике, генетике и селекции)
The article contains a comparative analysis of the taxonomical structure of the weedy species composition (segetal flora) in eight regions of Russian Federation: Leningrad, Novgorod, Vologda, Rostov and Sverdlovsk Provinces, Udmurt Republic, Republic of Bashkortostan, and Altai Territory. The segetal flora comprised weeds of cereals, root crops and perennial grasses. The comparison was made separately for the native and alien weeds. The number of native species was higher than that of alien species and varied from 137 to 209 species. The number of alien weeds varied from 99 to 179 species. Vologda Province had the lowest diversity of both native and alien plant species. Udmurt Republic had the greatest native species diversity and Altai Territory had the greatest alien species diversity. The Asteraceae, Poaceae, Brassicaceae, Fabaceae, Lamiaceae, Caryophyllaceae and Scrophulariaceae families dominated in both the native and alien fractions. The authors compared the compositions of species, families and genera of native and alien weeds. Native and alien weedy species showed the greatest similarity in their composition in geographically close regions: European Russia and the Urals. As for geographically remote regions – Altai Territory and Rostov Province – native and alien weedy species compositions were distant. At the same time, the levels of similarity among the native species were lower than among the alien ones. This attests to greater variability in the species composition among native weeds than among alien ones.